PENGUKURAN KINERJA PERUSAHAAN KONTRAKTOR TELKO DENGAN METODE BENCHMARKING: (STUDI KASUS PT. LUM) - Firdaus, Mohamad; Satma Rachendu (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
Telecommunication service providers consist of many entities. This results in a lot of business competition within it. It is very important to maintain the competitiveness of telecommunications companies to be able to continue to survive in this business environment. Therefore, companies need to conduct research that can identify hidden weaknesses of the company. This study aims to measure the performance of telecommunications contractor companies (Telco) by applying the benchmarking method, focusing on PT. LUM as a case study. Company performance will be evaluated in several key aspects, including operational efficiency, service quality, and customer satisfaction. Qualitative and quantitative approaches are used to collect and analyze data, including document analysis, interviews with senior management and customers, and literature studies on company performance and benchmarking. The results of the study are expected to provide a better understanding of PT. LUM's performance and allow for performance comparisons with other Telco contractor companies. Recommendations generated from this study are expected to help PT. LUM improve company performance and compete more effectively in the market